The Relationship of the Role of Mothers as Educators with Personal Hygiene Actions in Children in Rantau Selatan in 2020 - Maria Haryanti Butarbutar; Sri Lasmawanti; Rupina K. Situmorang; Ani Deswita Chaniago (Science Midwifery, 2022)
Personal hygiene or personal hygiene is an act to maintain the cleanliness and health of a person for the welfare, both physical and psychological. The purpose of this study is to determine the relationship of the role of mothers as educators with personal hygiene actions in children in Rantau Selatan in 2020. The research design used Analytic Survey with Cross-Sectional approach. The population were mothers who had elementary school children amounted to 100 respondents. The sampling used was purposive sampling with 50 respondents. Based on the results of data analysis using the Chi-Square Test, it showed that the significant probability value (Asymp.sig) was .016 < sig-value .05, this proved that there was a relationship between the role of mothers as educators with personal hygiene actions in children in Rantau Selatan in 2020. The conclusion showed that statistically there was a relationship between the relationship of the role of mothers as educators with personal hygiene actions in children in Rantau Selatan in 2020. It is recommended for mothers to care more and increase awareness of the importance of cleanliness, especially personal, family and environmental hygiene. And for research place society should get educating more about personal hygiene performance and the environment as well as facilitating more common hygiene activities such as cleaning the gutters. family and environmental hygiene. And for research place society should get educating more about personal hygiene performance and the environment as well as facilitating more common hygiene activities such as cleaning the gutters. family and environmental hygiene. And for research place society should get educating more about personal hygiene performance and the environment as well as facilitating more common hygiene activities such as cleaning the gutters.